Development of Differentiated Learning Module with Undo Procedure to Improve Learning Outcomes Students on Function Inversion Material - Muna Khairunnisa; Cita Dwi Rosita; Setiyani Setiyani; Mohd Hasril Amiruddin (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to develop a teaching module focusing on differentiated learning by applying the undo procedure to improve student learning outcomes and understanding of inverse functions. Method: This study is the development of a differentiated learning teaching module on the inverse function material using the four-D (4-D) model from Thiagarajan (Define, Design, Develop, and Disseminate). Meanwhile, to determine the effectiveness of the teaching module, the research subjects were students of class XI SMAIQu (Qurani Islamic High School) Al Bahjah Cirebon. Results: The teaching module based on the Undo procedure was considered valid by experts, with an average validation score reaching the very valid category. This module is very practical, as evidenced by its ease of use by teachers and students' high level of readability (80–90%). The module effectively improves student learning outcomes, with an average N-Gain Score of 0.65 (moderate to high category). The module supports differentiated learning, allowing students to learn according to their abilities. Novelty: This module uses the Undo procedure as a learning strategy, which has not been widely applied in developing mathematics teaching materials, especially for inverse function material. The module integrates the principle of differentiated learning, providing solutions to the diversity of student abilities in the classroom. The module is designed to help students understand concepts through a procedural approach, which is rarely focused on in conventional teaching modules.